دور المؤسسات الدينية في خدمة السنة النبوية في عصر الرقمنة دار الإفتاء المصرية نموذجا - Amr Mohammed Sayed Emam; Muhammad Ikram bin Abu Hassan; Fahmy Hossein Abdelkawy (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies